Availability of information and standard operating procedures affects the implementation of cigarette billboard regulation in Jember, East Java, Indonesia - Saiful, Brima Sahwa Sukma; Sandra, Christyana; Rokhmah, Dewi; Rochmawati, Ajeng Humami; Hidayah, Barika Isti’anatil (Universitas Udayana, 2022)
Background and purpose: Jember District has adopted a tobacco control policy, Jember Regent Regulation No. 27 Year 2013 that includes provision on regulating tobacco advertisement. This study aims to evaluate the policy implementation based on the availability of information and standard operational procedures (SOPs). Methods: This was a qualitative case study which was conducted in Jember District in 2020. Eleven informants were interviewed, consisted of policy actors, billboard building owner, tobacco factory, and student group for tobacco control. Data were collected through in-depth interview, observation, documentation, and triangulation. The data was then analysed thematically. Results: Information related to the policy was well comprehended by the implementers, but not by the community. The information is usually conveyed in conjunction with the coordination process between agencies, which is during field assessment. The observation for monitoring and evaluation in 2020 showed that there were tobacco billboards placed around the health facilities and government agencies, and one of them did not include the “18+” information. The SOP for this policy is the same as the standards for billboard installation permits in general. The barriers to this policy implementation were in regard to clarity of the main duties and functions of each implementer, especially when there was a violation, since it yet been outlined in the current SOP. Conclusion: Implementation of the regulation yet optimal from the availability of information and SOPs aspects. Policy dissemination as well as improvement on the SOP is needed to improve coordination process, monitoring, and evaluation.